Study Phenomenology Evaluation Joint Operation - Non Separate Vehicle using Profit Sharing Method in Expedition Companies - Permana Tedjo Dwi Pamungkas S.; Nur Fadjrih Asyik; Maswar Patuh Priyadi (Universitas Muhammadiyah Ponorogo, 2021)
The Sriwijaya Air airline is collaborating with five strategic partners under the auspices of Garuda Indonesia. This was realized in the form of a joint operation carried out by PT Citilink Indonesia with PT Sriwijaya Air and PT NAM Air where the collaboration ended on 31 October 2019 and left a trail of debts and debts. The importance of paying more serious attention to the treatment and process of operational cooperation (Joint Operations), in order to realize good corporate governance from the process of inquiry in the implementation of a merger or acquisition which is referred to as due diligence. In this study, researchers used a qualitative phenomenological approach. Phenomenology is an approach that focuses more on the concept of a particular phenomenon and the form of the study is to see and understand the meaning of an experience related to a particular phenomenon. The two companies are cooperating in Non-Administrative joint operation or there are no separate business entities from the two companies. In practice, the joint operation organizes its own special bookkeeping. Project Owner Bill submitted and agreed by each member of the joint operation, for Commercial Invoice, Tax Invoice, and proof of income tax article 23 to be on behalf of the company of the party organizing the joint operation bookkeeping. Along with the fulfillment of its VAT obligations, it is the responsibility of the party organizing the joint operation books.